Decompressive craniectomy in traumatic brain injury: Quo Vadis? - Moscote-Salazar, Luis Rafael; Alvis-Miranda, Hernando Raphael; Alcala-Cerra, Gabriel; Rubiano, Andres Mariano (Ukrainian Neurosurgical Journal, 2014)
Intracranial hypertension is the leading cause of mortality in patients with cranial injury. Currently the traumatic brain injury is a public health problem worldwide. Decompressive craniectomy emerges as a treatment strategy for patients with refractory intracranial hypertension. The completed surgery requires careful surgical technique and exquisite. We present a review of the literature about the technique.